2004
DOI: 10.1038/sj.bjc.6601711
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of cytotoxic T-lymphocyte precursor-oriented peptide vaccines for colorectal carcinoma patients

Abstract: In most protocols of peptide-based vaccination, no consideration has been paid to whether or not peptide-specific cytotoxic Tlymphocyte (CTL) precursors are pre-existent in cancer patients. Initiation of immune boosting through vaccination is better than that of immune priming to induce prompt and strong immunity. In this study, 10 human histocompatibility leukocyte antigen-A24 þ patients with advanced colorectal carcinomas were treated with up to four peptides that had been positive for pre-vaccination measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 37 publications
(33 reference statements)
1
29
0
Order By: Relevance
“…We previously reported that both IgG and CTL responses were augmented in the samples after 6 th vaccination from the majority of patients who showed PR responses. 19,23,25 We also demonstrated that there were no significant differences in overall survival between patients showing both CTL and IgG responses and those showing only IgG response. 10,11 These results suggest that boosted CTL responses are involved in tumor reduction, but not necessarily involved in prolonged overall survival.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 62%
See 2 more Smart Citations
“…We previously reported that both IgG and CTL responses were augmented in the samples after 6 th vaccination from the majority of patients who showed PR responses. 19,23,25 We also demonstrated that there were no significant differences in overall survival between patients showing both CTL and IgG responses and those showing only IgG response. 10,11 These results suggest that boosted CTL responses are involved in tumor reduction, but not necessarily involved in prolonged overall survival.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 62%
“…All of these peptides can induce HLA-A24-, A2-and A3-supertype-restricted and tumorspecific CTL activity in PBMCs of cancer patients. 6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][42][43][44] Before the first vaccination and 7 days after every sixth vaccination, 30 ml of peripheral blood was obtained and PBMCs were isolated by means of Ficoll-Conray density gradient centrifugation. Peptide-specific CTL precursors in PBMCs were detected using the previously reported culture method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[45][46][47][48] Several CEA-based vaccine formulations have proven to be safe in humans and not associated with autoimmune reactions, making vaccination of healthy individuals a potential approach for increasing the frequency of CEA-specific T cells in the donor hematopoietic cell graft. 31,[49][50][51][52] As for the vaccination of engrafted patients, timing of vaccine delivery could be critical for efficacy. Data obtained at different timepoints after transplantation suggest that full donor engraftment and discontinuation of immunosuppression will likely be important requirements for success.…”
Section: Discussionmentioning
confidence: 99%
“…The number of administered vaccinations varied widely, from 3 to 112 per patient, with the most prolonged vaccination periods being for the prostate cancer patients. Most of the safety, immune, as well as clinical responses in these studies have been previously reported (5)(6)(7)(8)(9)(10)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Studies are currently underway to obtain vaccination results for the treatment of pancreatic and breast cancer, as well as for the HLA-A3 supertype-positive patients.…”
Section: Methodsmentioning
confidence: 99%